METHOD DEVELOPMENT AND ITS VALIDATION FOR QUANTITATIVE DETERMINATION OF BOSENTAN IN TABLET DOSAGE FORM BY RP-HPLC - Shahul, Hameed M; Jat, R K; Indulatha, V N (Journal of Drug Delivery and Therapeutics, 2017)
Objectives of this research work were development and validation of HPLC methods of analysis for Bosentan in tablet dosage form from single components as per the current ICH & USP guidelines. HPLC methods also validated for the marketed Bosentan from single components. This developed procedure applied for regular analysis of these medicaments in pharmaceutical industry The major scope of research is development of simple, accurate, reproducible & fast cost effective methods for new cefalosporins. The methods are validated with recovery studies using bulk drug of 80%, 120% & 40%. Specific method is confirmed by checkingdinterference of expients & assay method. The interday & intraday assay are also performed for checking robustness of the system. The minimum detection limit is checked by using formula LOD = 3.3 sigma (St&nd deviation) / Slop, where σ indicate st&ard deviation & S denotes slop of the regression straight line. The wuantification limit is detrmined by using LOQ = 10 σ d(St&. dev.)/ S that is minimum concentration of drug can be quantified. Linearity is found in the limit of Beer’s law, straight line was constructed within the given range of the conc. of the drugs. So can develop & validate a new, reproducible, correct, & easy, less time consuming, cheap & ecofriendly method for daily analysis of drug in our general life. Keywords: Bosentan, RP HPLC, method development and validation.